O wieloznaczności monet typu DEAE SEGETIAE albo Segetia versus Segeta - Kluczek, Agata A. (Studia Europaea Gnesnensia, 2016)
The paper offers interpretations of the content of aurei and antoniniani of the DEAE SEGETIAE type, minted for Salonina Augusta, wife of emperor Gallienus (253–268). Apart from that instance, the name Segetia never appeared again in imperial coinage. Meanwhile, the effigy of the goddess on those coins displays traits found in the representations of other deities.